A novel 3D-Printed preferential posterior mitral annular dilation device delineates regurgitation onset threshold in an ex vivo heart simulator - Imbrie-Moore, Annabel M. (Med Eng Phys, 2020)
Mitral regurgitation (MR) due to annular dilation occurs in a variety of mitral valve diseases and is observed in many patients with heart failure due to mitral regurgitation. To understand the biomechanics of MR and ultimately design an optimized annuloplasty ring, a representative disease model with asymmetric dilation of the mitral annulus is needed. This work shows the design and implementation of a 3D-printed valve dilation device to preferentially dilate the posterior mitral valve annulus. Porcine mitral valves (n = 3) were sewn into the device and mounted within a left heart simulator that generates physiologic pressures and flows through the valves, while chordal forces were measured. The valves were incrementally dilated, inducing MR, while hemodynamic and force data were collected. Flow analysis demonstrated that MR increased linearly with respect to percent annular dilation when dilation was greater than a 25.6% dilation threshold (p < 0.01). Pre-threshold, dilation did not cause significant increases in regurgitant fraction. Forces on the chordae tendineae increased as dilation increased prior to the identified threshold (p < 0.01); post-threshold, the MR resulted in highly variable forces. Ultimately, this novel dilation device can be used to more accurately model a wide range of MR disease states and their corresponding repair techniques using ex vivo experimentation. In particular, this annular dilation device provides the means to investigate the design and optimization of novel annuloplasty rings.